2019
DOI: 10.1021/acs.orglett.9b03855
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Induced Difluoroalkylation of Alkynes and Alkenes

Abstract: The difluoroalkylation of alkynes and alkenes by direct photoexcitation of ethyl difluoroiodoacetate is described. Under catalyst- and oxidant-free conditions, iododifluoro­alkylation and hydrodifluoro­alkylation products were generated from alkynes, and difluoroalkylation products were prepared from alkenes. This methodology provides a streamlined access to difluoroalkylated organic compounds starting from simple alkynes or alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 66 publications
0
24
0
2
Order By: Relevance
“…Visible‐light induced difluoroalkylation of alkenes by direct photoexcitation of ethyl difluoroiodoacetate was reported by Fan and co‐workers (Scheme 37a) [109] . Interestingly, this protocol worked under catalyst‐ and oxidant‐free conditions.…”
Section: Miscellaneous Reactionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Visible‐light induced difluoroalkylation of alkenes by direct photoexcitation of ethyl difluoroiodoacetate was reported by Fan and co‐workers (Scheme 37a) [109] . Interestingly, this protocol worked under catalyst‐ and oxidant‐free conditions.…”
Section: Miscellaneous Reactionsmentioning
confidence: 90%
“…Visible-light induced difluoroalkylation of alkenes by direct photoexcitation of ethyl difluoroiodoacetate was reported by Fan and co-workers (Scheme 37a). [109] Interestingly, this protocol worked under catalyst-and oxidant-free conditions. It was found that the developed strategy selectively gave the difluoroalkylated and hydrodifluoroalkylation products from alkynes by the tuning the solvents (Scheme 37b).…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…[14] Copper-catalyzed CÀ H fluoroalkylation has been recognized as a powerful method to access complex fluorinated molecules and biomolecules. [15] On the other hand, direct CÀ H fluoroalkylation of coumarin derivatives by photoexcited catalysis, [16] palladium catalysis, [17] Rh(III) catalysis [18] and EDA complexes or halogen bond initiator [19] has proved to be capable for the post-modification of pharmaceutical significant molecules. Nevertheless, Cu-catalyzed CÀ H fluoroalkylation of heteroarenes, e. g. coumarin derivatives, has not been systematically investigated previously and the reaction yield was not satisfying (Scheme 2), [20] especially considering the appealing fact of utilizing fluoroalkylated heteroarenes as pharmacophores.…”
Section: Introductionmentioning
confidence: 99%
“…The significant advantages of this photochemical transformation are high efficiency, excellent functional group tolerance, and synthetic simplicity, thus providing a facile route for further application in pharmaceuticals and life sciences.Molecules 2020, 25, 508 2 of 8 mild, catalyst-free and operationally-simple strategy for the direct fluoroalkylation of olefins driven by the photochemical activity of electron donor−acceptor (EDA) complex between DMA and fluoroalkyl iodides. The significant advantages of this photochemical transformation are high efficiency, excellent functional group tolerance, and synthetic simplicity [52].…”
mentioning
confidence: 99%
“…Molecules 2020, 25, 508 2 of 8 mild, catalyst-free and operationally-simple strategy for the direct fluoroalkylation of olefins driven by the photochemical activity of electron donor−acceptor (EDA) complex between DMA and fluoroalkyl iodides. The significant advantages of this photochemical transformation are high efficiency, excellent functional group tolerance, and synthetic simplicity [52].…”
mentioning
confidence: 99%